2022
DOI: 10.3389/fimmu.2022.842069
|View full text |Cite
|
Sign up to set email alerts
|

Elevated SNRPA1, as a Promising Predictor Reflecting Severe Clinical Outcome via Effecting Tumor Immunity for ccRCC, Is Related to Cell Invasion, Metastasis, and Sunitinib Sensitivity

Abstract: Clear cell renal cell carcinoma (ccRCC) is the most common subtype of renal carcinoma and is associated with poor prognosis and notorious for its immune dysfunction characteristic. SNRPA1 is a spliceosome component responsible for processing pre-mRNA into mRNA, while the biological effect of SNRPA1 in ccRCC remains elusive. The aim of this study was to decipher the effect of SNRPA1 on clinical effect and tumor immunity for ccRCC patients. Multi-databases were collected to evaluate the different expression, pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…First of all, our research is mainly based on the public database, as a consequence of that, it lacked evidence from the laboratory data. Unlike some recent research studies, the research conducted by the Jiang et al not only explored the function of it based on the database but also successfully demonstrated the function of the SNRPA1 for the ccRCC cells; the research successfully demonstrated that knocking down the SNRPA1 made tumor cells less invasive [ 26 ]. Similarly, the research conducted by Gao et al had also used the same exploring pattern in the pan-cancer analysis of the PRDXs and demonstrated the pathway of the gene in the lab [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…First of all, our research is mainly based on the public database, as a consequence of that, it lacked evidence from the laboratory data. Unlike some recent research studies, the research conducted by the Jiang et al not only explored the function of it based on the database but also successfully demonstrated the function of the SNRPA1 for the ccRCC cells; the research successfully demonstrated that knocking down the SNRPA1 made tumor cells less invasive [ 26 ]. Similarly, the research conducted by Gao et al had also used the same exploring pattern in the pan-cancer analysis of the PRDXs and demonstrated the pathway of the gene in the lab [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…In more detail, LINC01087 seemed to interfere with 2 miRNAs targeting the messenger of C8orf37 (namely has-miR-644a and has-miR-7-5p), EFNA5 (hsa-miR-1305, hsa-miR-92a-3p), HOOK3 (hsa-miR-4505, hsa-miR-181a-5p), MYOZ3 (hsa-miR-7975, hsa-miR-197-3p), and PCP4L1 (hsa-miR-4505, hsa-miR-423-5p), with 3 miRNAs targeting the mRNAs of SLC2A3 (hsa-miR-606, hsa-miR-34a-5p, hsa-miR-98-5p) and SNRPA1 (hsa-miR-3174, hsa-miR-34a-5p, hsa-miR-98-5p), and 4 miRNAs interfering with the transcripts of IQCG (hsa-miR-3671, hsa-miR-181a-5p, hsa-miR-181b-5p, hsa-miR-181d-5p), PLAG1 (hsa-miR-569, hsa-miR-181a-5p, hsa-miR-181b-5p, hsa-miR-98-5p), and POLI (hsa-miR-4255, hsa-miR-19a-3p, hsa-miR-19b-3p, hsa-miR-92a-3p). Interestingly, most of these mRNAs and miRNAs have been connected to tumor suppressive and/or oncogenic functions in multiple cancers [ 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 ].…”
Section: Resultsmentioning
confidence: 99%
“…The gene SNRPA1 , a spliceosome component responsible for processing pre-mRNA into mRNA, showed strong prognostic potential in prostate cancer, HCC, and ccRCC [ 55 , 117 , 118 ]. Its oncogenic role in CRC has also been demonstrated [ 119 ].…”
Section: Discussionmentioning
confidence: 99%
“…With the rapid development of immunotherapy for ccRCC in recent years, resistance, increasing recurrence rates, and side effects have surfaced, and there are indications that new biomarkers or therapy target for predicting efficacy and prognosis are in urgent need of discovery [47]. Although ccRCC is deemed as immune cell infiltrationhigh tumor, it is also notorious for immune dysfunction and depletion [48][49][50]. It is urgent to comprehensively analyze the mechanism of this abrogated immunity phenomenon in ccRCC.…”
Section: Discussionmentioning
confidence: 99%